Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1523/jneurosci.19-12-04889.1999
|View full text |Cite
|
Sign up to set email alerts
|

Specification of Somatosensory Area Identity in Cortical Explants

Abstract: The H-2Z1 transgene is restricted to a subset of layer IV neurons in the postnatal mouse cortex and delineates exactly the somatosensory area. Expression of the H-2Z1 transgene was used as an areal marker to determine when the parietal cortex becomes committed to a somatosensory identity. We have shown previously that grafts dissected from embryonic day 13.5 (E13.5) H-2Z1 cortex and transplanted into the cortex of nontransgenic newborns express H-2Z1 according to their site of origin. Expression was not modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 44 publications
4
31
0
Order By: Relevance
“…However, at the cellular level, coexpression of H-2Z1 transgene with Satb1 was limited. We previously reported that H-2Z1 does not colocalize with Gad-67 transcripts or with the calcium binding proteins parvalbumin and calretinin in the cerebral cortex of P7 C57/CBA transgenics (Gitton et al, 1999a). In contrast, we find here that Satb1 is expressed in a subpopulation of cortical GABAergic interneurons, confirming the limited overlap between Satb1-and H-2Z1-positive cells.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, at the cellular level, coexpression of H-2Z1 transgene with Satb1 was limited. We previously reported that H-2Z1 does not colocalize with Gad-67 transcripts or with the calcium binding proteins parvalbumin and calretinin in the cerebral cortex of P7 C57/CBA transgenics (Gitton et al, 1999a). In contrast, we find here that Satb1 is expressed in a subpopulation of cortical GABAergic interneurons, confirming the limited overlap between Satb1-and H-2Z1-positive cells.…”
Section: Discussionsupporting
confidence: 84%
“…We observed a progressive extension of Satb1 labeling from the bottom of the barrels to more superficial regions of the barrelfield (Fig. 3B, P3 to P9), a pattern consistent with that of H-2Z1 in C57/CBA mice (Gitton et al, 1999a). Thus, the pattern of expression of H-2Z1 in C57/CBA transgenics consists in a subdomain of that of Satb1.…”
Section: Tangential Modulation Of Satb1 Expression In the Postnatal Csupporting
confidence: 69%
See 3 more Smart Citations